Pediatric ingested foreign body, acquired tracheoesophageal fistula – Endoscopic repair with cautery & fibrin glue (Tisseel): Case report and literature review - Victoria Valinluck Lao; Dan Lustig; Mark Boseley; Oliver Bennett Lao (Journal of Pediatric Surgery Case Reports, 2015)
Foreign body ingestion is common in the pediatric population and the mainstay of treatment is typically endoscopic removal. Complications such as tracheoesophageal fistula may occur due to foreign body ingestion. The treatment of tracheoesophageal fistula following foreign body ingestion is controversial. We report the case of a 33 month-old former 25 week-old triplet who developed a tracheoesophageal fistula following her foreign body ingestion. Following initial foreign body removal, subsequent treatment with electrocautery and fibrin sealant facilitated closure of the fistula as seen on repeat esophagram performed six weeks post-operatively. We report this case as a reminder of this complication and its association with foreign body ingestion as well as its insidious presentation and to encourage consideration of this modality as a primary treatment for acquired tracheoesophageal fistulae secondary to foreign body ingestion.